Equity and the crisis of development policy in developing countries: a critical analysis of the environment and climate change regulatory framework in Malawi - Banda, Gracian Zibelu (Department of Public Law, 2022)
This thesis examines the interface between development policy and the regulation of environment and climate change in developing countries, focusing on Malawi, its relevant policy and legislation. The central argument is that development, as adopted in Malawi and elsewhere in the developing world, carries power and knowledge asymmetries that structure risks and marginalises those on the periphery of policy discourse. As one commentator has observed, to be developed is to be enslaved by these discourses, including by the regulatory architecture that anchor these development narratives. This has negative implications for the application of equity norms despite its recognition in the Malawi Constitution as the basis for policy making. The thesis observes that a majority of people are marginalized and immiserated by the geographies and histories of vulnerability associated with dominant development paradigms. The applicable regulatory frameworks are not able to address this inequity primarily because they serve these paradigms. The climate change phenomenon has further exposed and exacerbated the limitations of the regulatory framework to deliver equitable development. But it has also provided an opportunity to address marginalisation mainly because the climate problem threatens all sectors regardless of interests, geography or history and, consequently, requires equity to be at the centre of the policy response. The thesis argues that in the Malawian context, a primary consideration in the design of a responsive environment and climate change regulatory framework is to understand and apply the development ethos as an empowering commitment based on the humanity and dignity of all Malawians as the Malawi Constitution mandates. Such an understanding of development essentially prioritizes the welfare and interests of the individual, the community and the state. The thesis highlights the utility of the right to development and its ethical, social justice and moral imperatives to reimagine human rights as ethical demands, rather than the current reliance on the juridical model. The thesis calls upon environmental human rights discourse to embrace equity norms and focus on those who are marginalized and vulnerable rather than the dominant juridical model of human rights jurisprudence that focuses on individual entitlements. The thesis further argues that the climate change problem has the potential to facilitate diverse participation in environmental regulation by emphasising the development losses associated with climate change. Focussing on climate justice can infuse equity norms to facilitate responsive environment and climate change regulation. It can also give voice to environmental institutions and galvanize regulatory capacity across sectors that have been marginalised in development regulation. The thesis argues that policy and legislation must address epistemic injustices inherent in the dominant development and environmental governance paradigms by engagement and contestation with lived realities of affected communities. This requires new ways of making policy and legislation which go beyond constituency representation and harnessing living customary norms that recognize and respond to geographies and histories of marginalisation and vulnerabilities.